2007
DOI: 10.1007/s11259-007-9005-y
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-mediated apoptosis in chicken postovulatory follicle regression

Abstract: Chicken postovulatory follicle (POF) regression occurs via the process of apoptosis. However, the signals and initiator pathways responsible for regression of the POF are unknown. In the current study, we examined gene expression patterns of various caspases (caspase-1, -2 and -3) involved in apoptosis by semi-quantitative RT-PCR. The percentage of apoptotic cells during POF regression was also quantified by flow cytometry. Expression of caspase-3 mRNA was noted in the largest preovulatory follicle (F1). Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…For example, removal of the most recent post-ovulatory follicle before it has completed regression delays oviposition of the egg derived from that follicle [ 24 ]. The post-ovulatory follicle regresses in an orderly fashion via apoptosis [ 50 ] in which caspases and macrophages play an important role [ 25 , 37 , 51 ]. Our observation of macrophages containing hemosiderin within late-stage regressing follicles is consistent with this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, removal of the most recent post-ovulatory follicle before it has completed regression delays oviposition of the egg derived from that follicle [ 24 ]. The post-ovulatory follicle regresses in an orderly fashion via apoptosis [ 50 ] in which caspases and macrophages play an important role [ 25 , 37 , 51 ]. Our observation of macrophages containing hemosiderin within late-stage regressing follicles is consistent with this.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of macrophages containing hemosiderin within late-stage regressing follicles is consistent with this. Regression in the laying hen takes about 4–6 days [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, follicles selected to enter the pre-ovulatory hierarchy rarely undergo atresia and the granulosa cells are highly resistant to apoptosis[ 30 , 31 ]. Similar to mammalian corpus luteum, the post-ovulation follicles degenerated mainly through apoptosis process [ 32 , 33 ]. The comparisons of follicle cells from different phases of the ovulation cycle could enable us to identify the cell death or survival factors in the follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Some molecular events involved in programmed cell death are largely mediated by caspases (see review JOHNSON 1996;JOHNSON & BRIDGHAM 2002). The caspase family includes initiator caspase (-1, -2, -8, -9, -10) and effector caspase (-3, -6, -7) and it was found that caspase-1, -2 and -3 play the essential role in the regression of chicken reproductive tissue SUNDARESAN et al 2008). Thus, to ex- amine whether TCDD and PCBs affects cell apoptosis in the chicken shell gland the initiator caspase-1 and executioner caspase-3 mRNA expression was determined.…”
Section: Discussionmentioning
confidence: 99%